Gradient based variable forgetting factor RLS algorithm - So, C.F.; Ng, S.C.; Leung, S.H. (Signal processing, 2003)
An accurate new variable forgetting factor recursive least-square adaptive algorithm is derived. An improved mean square behaviour analysis is presented, which shows that the theoretical analysis and the simulation results are close to each other. The control of the forgetting factor is based on the dynamic equation of the gradient of mean square error. Compared with other variable forgetting factor algorithms, the new algorithm provides fast tracking and small mean square model error, and its performance will not be degraded much even in low signal-to-noise ratios.